Relationship between organization culture and the success of an organization in becoming a learning organization - Ng, Nee Nee (Universiti Malaysia Sarawak, UNIMAS, 2011)
The purpose of this study was to identify the relationship between organization culture and the success of an organization in becoming a learning organization. Specifically, it was aimed to find out if there was any relationship between organizational culture factors and success of an organization in becoming a learning organization. The factors concerned were organizational values, leadership, communication, work environment, motivation, and trust. The research methodology used was a quantitative survey method where questionnaire was utilized to collect data. The collected data was analyzed using software Statistical Package for Social Sciences (SPSS) version 17.0 which covered descriptive statistics and inferential statistics. Descriptive statistics in terms of frequency and percentage were used to determine the distribution of respondents' demographic characteristics. The hypotheses statements were analyzed using Pearson Correlation Coefficient (Inferential Statistic). Result of the study showed that all the tested independent variables (organizational values, leadership, communication, work environment, motivation, and trust) were significantly related to the success of an organization in becoming a learning organization. The study concluded with some recommendations that would allow improvement of learning organization and future research. Human resource practitioners were recommended to take organization culture into consideration when implementing a learning organization. Apart from that, future researchers were suggested to conduct their research in more than one company, complement their study with qualitative research methodology, and focus on other factors of organization culture which were not covered in this study.